2018
DOI: 10.1002/prep.201700281
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Eccentric Initiation on the Fragment Velocity Distribution of D‐Shaped Casings Filled with Explosive Charges

Abstract: Irregular casings filled with explosive charges are increasingly being developed for the designs of new warheads and explosive protection. In this work, we studied the fragment velocity of a semicircular D-shaped casing, which is a typical asymmetric casing. Static explosive experiments were conducted with D-shaped casings with different eccentric detonation coefficients (1/8, 3/8, 5/8, and 7/8) to determine their circumferential fragment velocity distributions. An empirical formula was then established to cal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 10 publications
(15 reference statements)
0
4
0
Order By: Relevance
“…Recently, scholars have carried out much research on the fragment scattering characteristics and detonation driving principle of the asymmetric charge structure. Guo [2] carried out the experimental study and numerical calculation about the effect of eccentric initiation on the velocity distribution of the D-shaped charge fragments, which found the phenomenon of secondary loading of the reflected detonation wave in the D-shaped charge established empirical model. Li [3] carried out related research on the fragments scattering characteristics of a hexagonal charge structure.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, scholars have carried out much research on the fragment scattering characteristics and detonation driving principle of the asymmetric charge structure. Guo [2] carried out the experimental study and numerical calculation about the effect of eccentric initiation on the velocity distribution of the D-shaped charge fragments, which found the phenomenon of secondary loading of the reflected detonation wave in the D-shaped charge established empirical model. Li [3] carried out related research on the fragments scattering characteristics of a hexagonal charge structure.…”
Section: Introductionmentioning
confidence: 99%
“…In the past few decades, researchers have successively carried out research on directional fragmentation warheads using eccentric detonation, explosive deformation and expansion [1][2][3], and obtained relevant research results. They also tried to improve the payload ratio and lethal power by designing a special-shaped warhead [4][5][6][7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…In the field of research on directional warheads, Feng SS [1] studied the radial distribution of fragment velocity under the eccentric initiation of an axisymmetric warhead, and established a calculation formula for the radial distribution of fragment velocity; Wang L [2] studied radial distribution of fragment velocity under double-point eccentric initiation, and proposed the formula for calculating the fragment velocity; Yang YD [3] performed a numerical simulation of the deforming processes of deformable warhead, and obtained the matching relationships of the deformation control parameters. In the field of research on special-shaped warheads, Li XY [4] studied the energy distribution characteristics of the D-shaped prefabricated fragment warhead through experiments, and gave the calculation formula of the power field; Ding LL [5] studied the dispersion rule of fragments about the asymmetric shell to internal blast loading by experimental and numerical methods, and it is found that the convex and concave structures will lead to the divergence and convergence of fragments respectively; Guo ZW [6][7] studied the shell fragmentation and velocity distribution of the small aspect ratio and large aspect ratio D-shaped warheads under different eccentric initiation coefficients by numerical simulations and pulsed X-ray experiment, and the velocity calculation model is established; Wu JB [8] studied the fragmentation driving process and fragment scattering characteristics of the hex style warhead under eccentric initiation, and found it can significantly improve the fragment scattering density in the target direction; Ning JG [9] conducted an experimental study on the explosion process of the triangular prism-shaped prefabricated fragment warhead, and proposed a modified formula to calculate the velocity of the fragment; Deng YX [10] studied the expand-rupturing process of the elliptical cross-section natural fragment warhead shell driven by detonation, and obtained the radial velocity distribution law of fragments. In this paper, a non-rotational warhead suitable for ground attack blast-fragmentation warheads such as UAV and cruise missiles was designed.…”
Section: Introductionmentioning
confidence: 99%
“…Intending to study the influence of noncircular geometry on the fragment velocity, Ding [5], Guo [6][6] [7], Ning [8], and Marriott CO [9] studied the distribution of the fragment velocity of projectiles such as D-shape and prismatic projectiles. They found that during eccentric initiation, the detonation wave propagation was similar to that in a noncircular section, and the fragment velocity was no longer uniform.…”
Section: Introductionmentioning
confidence: 99%